Interference of psychomotor and spatio-temporal parameters on the efficiency of motor actions involved in the eastern species physical culture - Yong Qiang Liu (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to identify interferences psychomotor abilities for consistency in the management of spatio-temporal parameters of procedural and final precision in the movements with complex motor structure. Material : the study involved 30 people occupying the eastern species physical culture (Wushu Qigong and Tai Chi Chuan). Results : It was found that the identified trusted connection as positive (n = 59, r = 0.63 to 0.92) and negative (n = 21, r = from -0.63 to -0.89) confirm the influence of particular classes in the eastern system ability to coordinated control movements of different coordination complexity. Conclusions : the ability to control the internal forces, the ability to focus, alertness and mind control depend on three complementary levels - substance "Jing", "Qi" and "Shen", which directly affect the state of psychomotor sphere and target accuracy of spatio-temporal motion parameters.